Pengaruh Mindfulness Terhadap Depresi Remaja - Roland Lekatompessy (Indonesian Journal of Nursing Scientific, 2023)
The effect of mindfulness on adolescent depression. Mental health problems include depression are a major cause of disease in adolescents worldwide. Because the majority of mental health problems experienced by adults begin in childhood, focusing on the mental health of children and adolescents should be a global priority. Training dan development program is the way to support adolescent mental health. One such program is mindfulness, which is self-therapy that focuses on present conditions without judging the past, present, or future. The study aim to determine the impact of mindfulness on adolescent depression. This is a quantitative study with 12 adolescent from Latuhalat Sunday School who are depressed as sample. Purposive sampling technique was used to sampling, and the data was analyzed using the wilcoxon test. The study's findings revealed that mindfulness can help reduce adolescent depression. this article can serve as a guideline for overcoming teenage depression through mindfulness for readers in general and health workers in particular.